Variants in the DNAH11 gene responsible for primary ciliary dyskinesia or probably atypical primary ciliary dyskinesia presenting left-right asymmetry disorder - Kai Zhao; Lamei Yuan; Ying Xiong; Hong Xia; Sheng Deng; Ming Chen; Yunjie Liao; Jiangang Wang; Hao Deng (PLoS ONE, 2026)
Primary ciliary dyskinesia (PCD) is a rare multi-system cilia-related disorder, and approximately 50% of individuals with PCD exhibit left-right asymmetry disorder. The dynein axonemal heavy chain 11 gene ( DNAH11 ) pathogenic variants are responsible for primary ciliary dyskinesia 7, with or without left-right asymmetry disorder. This study aimed to detect the pathogenic variants in three unrelated patients diagnosed with PCD or left-right asymmetry disorder based on the clinical and imaging examinations. Whole exome sequencing, Sanger sequencing, and comprehensive bioinformatics analyses were performed. Seven DNAH11 heterozygous variants, which involved evolutionarily conserved residues and were predicted to exert deleterious effects, reduce protein stability, change protein conformation, and affect non-covalent residue’s interactions, were identified as potential pathogenic factors responsible for these patients, respectively. In patient 1, three variants in compound heterozygotes, c.[3541A > G];[4334G > A;12428T > C] (p.[(Ser1181Gly)];[(Arg1445Gln;Met4143Thr)]), were confirmed. In patient 2, two variants in potential compound heterozygotes, c.2912A > G(;)7980A > T (p.(Asp971Gly)(;)(Gln2660His)), were detected. In patient 3, two variants in compound heterozygotes, c.[845T > C];[11402C > G] (p.[(Met282Thr)];[(Pro3801Arg)]), were confirmed. The phenotypes observed in these patients are consistent with typical/probably atypical PCD or DNAH11 -associated ciliopathy, although functional validation is needed to confirm variant pathogenicity. These findings expand the phenotypic spectrum of DNAH11 variants and may facilitate more accurate genetic diagnosis and counseling.